Efficiency Improvement in Raw Material Inventory Management Using EOQ and POQ (Study Case: PT. Varia Usaha Beton) - Tsania Lutfia Salsabila Ali Tamam; Fourry Handoko; Sony Haryanto (JTI: Jurnal Teknik Industri, 2025)
This study aims to calculate the need for inventory and ordering of raw materials for concrete production at PT. Varia Usaha Beton optimally so that there is no excess or shortage of inventory to minimize total costs using the EOQ and POQ methods, and comparing the EOQ and POQ methods that will be applied. This study is a descriptive study with a quantitative approach. Data collection is carried out using observation and interview techniques. The results of this study show that by the EOQ method, the quantity of cement raw material orders is 3,109.01 tons with an ordering period of 3 times per year and a total inventory cost of Rp124,110,362.54. Then, in the POQ method, the quantity of cement raw material orders is 708.12 tons with an ordering frequency of 12 times in one year, with an annual inventory cost of Rp368,875,317.77. With the EOQ method, the quantity of raw materials ordered for sand is 9,630.01 tons with an ordering period of 3 times per year and a total inventory cost of Rp 126,473,726.00. Then, in the POQ method, the quantity of raw materials ordered for sand is 2,515.78 tons, with an ordering frequency of 12 times in one year, with an annual inventory cost of Rp 368,875,317.77. With the EOQ method, the quantity of raw materials ordered for stone is 8,383.57 tons with an ordering period of 3 times per year and a total inventory cost of Rp 111,871,065.21. Then, in the POQ method, the quantity of raw materials ordered for stone is 2,429.67 tons, with an ordering frequency of 12 times in one year, with an annual inventory cost of Rp 242,855,765.96. Thus, using the EOQ method produces a lower total cost than the POQ method, by implementing the EOQ method in managing raw material inventory at PT. Varia Usaha Beton in 2023 is projected to save 80.5% of the previous costs on cement raw materials, 80.8% on sand raw materials, and 81% on stone raw materials. Keywords: Inventory Control, Inventory, Economic Order Quantity, Periodic Order Quantity